Molecular Evaluation of Viral load and Genotype of HCV in Acute and Chronic HCV Patients in Kirkuk City - Israa Saadoon; Thekra Hamada; Muhannad Alazzawy (Kirkuk Journal of Science, 2019)
The study aimed at detection of HCV load and genotypes in acute and chronic HCV patients. A cross sectional study was carried out in Kirkuk city from 15th of March 2017 to 15th of November 2017. The number of hepatitis patient understudy were 62 hepatitis C (27 acute and 35 chronic) whose ages were between 20-75 years old. These patients admitted to Hepatology and Gastroenterology centers of Kirkuk. The control group who were matched to the patients studied, included 30 individuals who admitted to blood bank for blood donation. The study showed that no statistical differences between acute and chronic HCV concerning their viral load and the highest viral load mean was found in acute HCV patients (1162.6 v.s 1234.3) IU/ml. In the current study, the high rates of chronic and acute HCV patients were infected by genotype 4 of HCV (68.69% and 63.63% respectively) and the lowest rate were genotype 1a. The study showed that there was a highly significant difference between viral loads of acute and chronic HCV patients as regarding genotype 1a (1298.7 v.s. 1155.4 IU/ml), ( P: 0.001), the study showed a significant difference between viral loads of acute and chronic HCV patients concerning genotype 4 and a significant relation of viral loads of acute HCV infection with genotype 1a and genotype 4. It was concluded that the was no difference HCV load in acute and chronic infection and genotype 4 as the most frequent HCV genotype in Kirkuk